INFLUENCE PRICE DISCOUNTS AND COMPLETENESS OF PRODUCTS AGAINST PURCHASING DECISIONS AT THE WS PERFUME SHOP IN BENGKULU CITY - Anggi Josetio Prayoga; Ade Tiara Yulinda (International Journal of Accounting, Finance and Business, 2023)
This study aims to determine the effect of price discounts and product completeness on purchasing decisions at the WS Perfume Shop in Bengkulu City. This research is a type of research using a quantitative approach. The sample in this study amounted to 110 respondents with the accidental sampling method. Data collection techniques in this study used observation, interviews, and questionnaires. The data analysis technique in this study uses Multiple Linear Regression Analysis, Classical Assumptions Test, t-test and F-test. The results of this study indicate that the Discount Price variable partially has a significant effect on purchasing decisions, the Product Completeness variable partially has a significant effect on decisions Purchasing, then the variable Price Discount and Product Completeness Simultaneously have a significant influence on Purchasing Decisions.